Cell-Type-Specific Heat-Induced Changes in the Proteomes of Pollen Mother Cells and Microspores Provide New Insights into Tomato Pollen Production Under Elevated Temperature - Priya Thapa; Jun Guo; Kajol Pradhan; Dibya Thapa; Sudhakar Madhavarapu; Jing Zou; Jesse Potts; Hui Li; Joshua O’Hair; Chen Wang; Suping Zhou; Yong Yang; et al. (Proteomes, 2025)
Background: Tomatoes are self-pollinating plants, and successful fruit set depends on the production of functional pollen within the same flower. Our previous studies have shown that the ‘Black Vernissage’ tomato variety exhibits greater resilience to heat stress in terms of pollen productivity compared to the ‘Micro-Tom’ variety. Pollen productivity is determined by meiotic activity during microsporogenesis and the development of free microspores during gametogenesis. This study focused on identifying heat stress (HS)-induced proteomes in pollen mother cells (PMCs) and microspores. Methods: Tomato plants were grown under two temperature conditions: 26 °C (non-heat-treated control) and 37 °C (heat-treated). Homogeneous cell samples of meiotic PMCs (prior to the tetrad stage) and free microspores were collected using laser capture microdissection (LCM). The heat-induced proteomes were identified using tandem mass tag (TMT)–quantitative proteomics analysis. Results: The enrichment of the meiotic cell cycle in PMCs and the pre-mitotic process in free microspores confirmed the correlation between proteome expression and developmental stage. Under HS, PMCs in both tomato varieties were enriched with heat shock proteins (HSPs). However, the ‘Black Vernissage’ variety exhibited a greater diversity of HSP species and a higher level of enrichment compared to the ‘Micro-Tom’ variety. Additionally, several proteins involved in gene expression and protein translation were downregulated in PMCs and microspores of both varieties. In the PMC proteomes, the relative abundance of proteins showed no significant differences between the two varieties under normal conditions, with very few exceptions. However, HS induced significant differential expression both within and between the varieties. More importantly, these heat-induced differentially abundant proteins (DAPs) in PMCs are directly involved in meiotic cell division, including the meiosis-specific protein ASY3 (Solyc01g079080), the cell division protein kinase 2 (Solyc11g070140), COP9 signalosome complex subunit 1 (Solyc01g091650), the kinetochore protein ndc80 (Solyc01g104570), MORC family CW-type zinc finger 3 (Solyc02g084700), and several HSPs that function in protecting the fidelity of the meiotic processes, including the DNAJ chaperone (Solyc04g009770, Solyc05g055160), chaperone protein htpG (Solyc04g081570), and class I and class II HSPs. In the microspores, most of the HS-induced DAPs were consistently observed across both varieties, with only a few proteins showing significant differences between them under heat stress. These HS-induced DAPs include proteases, antioxidant proteins, and proteins related to cell wall remodeling and the generation of pollen exine. Conclusions: HS induced more dynamic proteomic changes in meiotic PMCs compared to microspores, and the inter-varietal differences in the PMC proteomes align with the effects of HS on pollen productivity observed in the two varieties. This research highlights the importance of the cell-type-specific proteomics approach in identifying the molecular mechanisms that are critical for the pollen developmental process under elevated temperature conditions.